AN URBAN PRIMARY HEALTHCARE DELIVERY SYSTEM - Jain, Vivek; Das, Shiba; Koyyala, Ashwith; Kumar, Ashwini (ShodhKosh: Journal of Visual and Performing Arts, 2022)
With this study, we aim to look at the Mohalla Clinics of Delhi as a model of a primary health care system in Delhi’s urban fabric. This study will uncover the contributions of this particular model concerning primary healthcare and try to establish the importance of Primary Health Care in an urban scenario. The secondary research data comprises of research papers and newspaper articles that follow the history and issues surrounding Mohalla Clinics and delivery mechanisms. The primary data comprises of on-site interviews, surveys, photography, videography and architectural documentation. Based on the data collected, we have a comprehensive understanding of the clinics as an individual entity and the collective role that they play in the larger context. We undertook an analysis to understand how the Mohalla Clinic model is effective as an urban primary health care system, and how every clinic works as a self-contained cuboid providing healthcare services to people. Consequently, we have been able to establish the various factors affecting this healthcare model and their direct relation with different levels of healthcare delivery systems. The larger implication of this study can be envisaged as to how this model has helped in improving Primary Health Coverage across the city.